Modelling trust evolution within small business lending relationships - Ying Tang; Andrea Moro; Sandro Sozzo; Zhiyong Li (Financial Innovation, 2018)
Trust is a key dimension in the principal-agent relationship and it has been studied extensively. However, the dynamics, evolution, and intrinsic motivation and mechanisms have received less attention. This paper investigates the intrinsic motivation of trust and it proposes a theoretical model of trust evolution that is based on the notion of 'trust response' and 'trust spiral'. We then specifically focus on trust within the lending relationship between banks and small businesses, and we run numerical simulations to further illustrate the evolution of involved mutual trust over time. Our model provides implications for future research in both trust evolution and small business lending relationships.
Keywords: 650; Trust; Spiral; Small business lending; Reciprocity; Altruism